2022
DOI: 10.1038/s41598-022-24286-3
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous adverse events in patients treated with PD-1/PD-L1 checkpoint inhibitors and their association with survival: a systematic review and meta-analysis

Abstract: Immune-related cutaneous adverse events (irCAEs) in patients treated with programmed cell death-1/programmed death-ligand 1 (PD-1/PD-L1) checkpoint inhibitors may be associated with better clinical outcomes. However, the extent to which these results can be extrapolated to all tumour types remains unclear. Herein, we conducted a meta-analysis of patients with cancer receiving anti-PD-1/PD-L1 immunotherapy, to determine the cumulative incidence of irCAEs and their association with survival. We systematically se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…A positive correlation between irAEs and the development of ORR, PFS, and OS in patients treated with ICIs has been reported in the literature (Hussaini et al 2021 ; Zhao et al 2022 ). The results of this paper showed that the occurrence of irAEs was associated with patients’ OS.…”
Section: Discussionmentioning
confidence: 72%
“…A positive correlation between irAEs and the development of ORR, PFS, and OS in patients treated with ICIs has been reported in the literature (Hussaini et al 2021 ; Zhao et al 2022 ). The results of this paper showed that the occurrence of irAEs was associated with patients’ OS.…”
Section: Discussionmentioning
confidence: 72%